“English Speaking Club” Pendampingan Untuk Meningkatkan Kepercayaan Diri Dan Kualitas Speaking Mahasiswa Program Studi Tadris Bahasa Inggris Fakultas Tarbiyah Dan Keguruan Iai Darussalam Blokagung - Faiqotur Rizkiyah; Dewi Khawa; Syarifah Robiatul Munawaroh; Annisa Fitria Mukaromah (IAI Darussalam, 2023)
The underlying of this community service is the TBIG students’ inability to speak English well. This is due to their lack of self-confidence, lack of vocabulary and practice. It is necessary to overcome through English Speaking Club program. The mentoring method used is Asset-based Community Development (ABCD) which views the community as potential people. The results show that students' speaking ability improves. This improvement is shown by positive changes in terms of vocabulary and pronunciation. Their Vocabularies are increasingly varied and the pronunciation is also precise. Meanwhile, Students' self-confidence also improves. As their vocabularies increase, students feel more confidence to communicate and speak English in public. The fear and lack of confidence toward their ability slowly disappears. Furthermore, the English tutor's ability improves. This improvement can be seen from the micro teaching which was followed after the workshop activities. They shared their experiences with each other on how to open and animate the class atmosphere and close the class